A Differentiated Instruction Implementation in EFL Second-ary School : (Case Study: SMA Islam Plus Adzkia) - Masniati Murni; Zubaidah Hanum (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The topic of Differentiated Instruction (DI) has recently been studied by researchers and practitioners due to its importance and potential to improve student learning. In this regard, the current study aims to provide a concise overview of DI in the context of EFL to illustrate the need for its implementation in the classroom to foster successful language learning. Since differentiated instruction is designed to place students at the centre of the teaching and learning process, promote equity and academic success, as well as recognize diversity among students, it enables teachers to address a student’s unique needs, interests, abilities, English proficiency, and preferred learning strategies. While challenges such as increased workload and implementation pressure in DI may arise, the potential benefits of this approach to students' learning processes, attitudes toward learning, and long-term success are notable. Therefore, the learning process is maximized when teachers are committed to differentiated instruction. SMA ISLAM PLUS ADZKIA (SIPA) is one of the most popular spotlight of school in Medan which the school was succeed in graduating their Alumni to Kedinasan and private university both inside and outside the country with scholarship. This school becomes the spot or role model for many other schools in Medan, therefore, the researcher intended to investigate further about the teaching model applied in this school, especially in EFL classroom in studying English. Some problems need to be answered after applying this study, such as how the English teachers manage the class to apply the DI, how is the students’ understanding about the subject after they applied DI